If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p = 3(t + 4) + -1t Reorder the terms: 6p = 3(4 + t) + -1t 6p = (4 * 3 + t * 3) + -1t 6p = (12 + 3t) + -1t Combine like terms: 3t + -1t = 2t 6p = 12 + 2t Solving 6p = 12 + 2t Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '6'. p = 2 + 0.3333333333t Simplifying p = 2 + 0.3333333333t
| 8x^2-13=-8 | | 22-(x+5)=7x-7 | | 4x-14-6x+4=6-8x-8+2x | | 3y-5=5y+4 | | 6m^2+5m-4= | | 5d-d= | | 21.20-106= | | 4m^2+5=-57 | | 4x+39+12x-17=180 | | x+x+11=83 | | 7y-13-4y+8=0 | | A+1=37+a | | 7x^2+0.5x=0 | | 6x-5=18x+1 | | -20+17g=1-g | | 5p^2+4=429 | | x+x+7=65 | | 3w-1=6w-5 | | .5(4x+4)-(x-8)= | | 7(9+4x)=-105 | | 7x^2+.5x=0 | | 2(9)+(3)= | | 28=3(1+x)+5(-x+5) | | 8+5x=52x | | x^12*x-8=0 | | 2x^2+88=(2x+4)(x+4) | | 2x^2+88=2x^2+12x+8 | | 6m-2y=3y-2 | | 2+3(-6+4)=8 | | n+10-6=7 | | 4(v+4)-7v=-14 | | M-7m-9m+2= |